Apelin Increases Cardiac Contractility via Protein Kinase Cε- and Extracellular Signal-Regulated Kinase-Dependent Mechanisms - Perjés, Ábel; Skoumal, Réka; Tenhunen, Olli; Kónyi, Attila; Simon, Mihály; Horváth, Iván G.; Kerkelä, Risto; Ruskoaho, Heikki; Szokodi, István (PloS one, 2014)
Apelin, the endogenous ligand for the G protein-coupled apelin receptor, is an important regulator of the cardiovascular homoeostasis. We previously demonstrated that apelin is one of the most potent endogenous stimulators of cardiac contractility; however, its underlying signaling mechanisms remain largely elusive. In this study we characterized the contribution of protein kinase C (PKC), extracellular signal-regulated kinase 1/2 (ERK1/2) and myosin light chain kinase (MLCK) to the positive inotropic effect of apelin. In isolated perfused rat hearts, apelin increased contractility in association with activation of prosurvival kinases PKC and ERK1/2. Apelin induced a transient increase in the translocation of PKCε, but not PKCα, from the cytosol to the particulate fraction, and a sustained increase in the phosphorylation of ERK1/2 in the left ventricle. Suppression of ERK1/2 activation diminished the apelin-induced increase in contractility. Although pharmacological inhibition of PKC attenuated the inotropic response to apelin, it had no effect on ERK1/2 phosphorylation. Moreover, the apelin-induced positive inotropic effect was significantly decreased by inhibition of MLCK, a kinase that increases myofilament Ca2+ sensitivity. Apelin increases cardiac contractility through parallel and independent activation of PKCε and ERK1/2 signaling in the adult rat heart. Additionally MLCK activation represents a downstream mechanism in apelin signaling. Our data suggest that, in addition to their role in cytoprotection, modest activation of PKCε and ERK1/2 signaling improve contractile function, therefore these pathways represent attractive possible targets in the treatment of heart failure.